Yield Gap Analysis of Chickpea Productivity through Front Line Demonstrations in Sagar District of Madhya Pradesh - A.K. Tripathi, K.S. Yadav, Mamta Singh and D.K. Singh, (Indian Journal of Extension Education, 2018)
The frontline demonstrations on proven technology on chickpea was conducted on 80 farmer’s fields in the sixvillages of Sagar district of Bundelkhand region of Madhya Pradesh during rabi seasons of 2012-13 to 2013-14 under rainfed condition on medium to heavy soil with medium fertility status. Demonstration was conductedunder Soybean – Chickpea cropping system to study the productivity enhancement of Chickpea through improvedproduction technologies. The results revealed that integrated crop management practices reduced the wiltincidence reduced from 10.45 to 4.05 per cent (61.2 per cent) and larval population of Gram pod borerdecreased from 1.2 to 0.50 per plant (58.3 per cent) in both the years. The average 45-46 pods per plant wereobtained under improved technology over to farmer’s practices (36-40). The seed yields of chickpea underimproved technology ranged between 9.83 q ha-1 to 15.79 q ha-1 with increase in seed yields by 22.8 and 39.8per cent in both the years. The average seed yields under improved technology were 12.81 q ha-1 as againstfarmers practice where seed yield was 9.94 q ha-1. On an average an additional cost Rs. 1376 ha-1 withimproved package given additional benefits of Rs. 8795/ha from chickpea crop . However, maximum averagenet returns (Rs.37588 ha-1) as well as benefit cost ratio (4.61) were recorded under improved technologies ascompared to farmer’s practice (Rs.28793 ha-1 and 4.18). Technology gap of 319 kg/ha and extension gap of291 kg/ha were found in chickpea production due to differential in feasibility of recommended technologies,lack of awareness, timely unavailability of quality input at farmers level.